Responses of Antioxidant Defenses in Coprinus comatus Exposed to Cadmium and Mercury Toxicity - Cen, Feng; Hu, Yuanjia; Xu, Heng (Asian Journal of Chemistry, 2012)
Pot culture experiments using Coprinus comatus were conducted to study the effects of soil cadmium or mercury concentrations (at doses of 0.5, 1.5, 5.0 and 15.0 mg kg-1) on the growth, the metal accumulation, soluble proteins, lipid peroxidation, thiol compounds and the activities of antioxidant enzymes. The results showed that the biomass and soluble protein content of C. comatus were inhibited by Cd and Hg, but the presence of metals enhanced lipid peroxidation in stipes and caps. Both Cd and Hg were readily accumulated by fruit bodies, and their contents were greater in the caps than those in the stipes. Thiol compounds and antioxidant enzyme activities [catalase (CAT) and peroxidase (POD)] were induced by soil Cd, while the levels increased with Hg concentrations up to a maximum value and then decreased. However, superoxide dismutase (SOD) activity was enhanced exposed to both Cd and Hg.